2020
DOI: 10.1038/s41598-020-68058-3
|View full text |Cite
|
Sign up to set email alerts
|

A new role for anandamide: defective link between the systemic and skin endocannabinoid systems in hypertrophic human wound healing

Abstract: The use of cannabinoids to treat fibrotic skin diseases is an emergent issue. Therefore, we aimed to evaluate systemic and skin endocannabinoid responses in the wound-healing process in humans. A prospective study was performed in 50 patients who underwent body-contouring surgery. Anandamide (N-arachidonoylethanolamine, AEA), 2-arachidonoylglycerol (2-AG), palmitoylethanolamide (PEA) and oleoylethanolamide (OEA) were quantified using LC-MS/MS. Ten (20%) patients developed hypertrophic (HT) scars. No significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 64 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…We established reference concentrations of PEA, OEA and AEA in all tested tissues, including AM and PL, by averaging values from the central and peripheral part of placenta, which did not differ in their statistical signi cance (Supplementary Table S4). An observed trend in the distribution of NAEs through all measured specimens (PEA > OEA > AEA) is in accordance with previously published results [22,25,53].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We established reference concentrations of PEA, OEA and AEA in all tested tissues, including AM and PL, by averaging values from the central and peripheral part of placenta, which did not differ in their statistical signi cance (Supplementary Table S4). An observed trend in the distribution of NAEs through all measured specimens (PEA > OEA > AEA) is in accordance with previously published results [22,25,53].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, they may be at least partially responsible for the positive effects associated with AM/ACM in the healing process. It is known that PEA operates primarily through PPAR-α receptor, which is expressed also in the skin [53], the site where AM/ACM grafts are applied. It has been shown that activators of PPAR-α receptor promote differentiation of human epidermal keratinocytes [67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, UV radiation has a strong effect on the endocannabinoid system in the skin fibroblasts and keratinocytes, which includes both decreases in basal endocannabinoid (anandamide, 2-AG) levels as well as enhanced expression of their main membrane receptors (CB1/2, TVRP1) [ 3 , 6 ]. So far, the direct role of endocannabinoids in human skin has been described in the case of wound healing [ 7 ], but also under neo-plastic processes [ 8 ], where its increased level promoted cell proliferation and has an antiapoptotic effect. However, their basic action concerns the interactions with specific receptors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%